A fotografia e o processo de construção social da memória - Sergio Luiz Pereira da Silva (Ciências Sociais Unisinos)
The photograph as a document is almost always linked to memory, a visual memory that portrays, re-signifies and re-contextualizes the social action of the look. In this sense the photographer is a social actor who, among other things, intrumentalizes the look by highlighting aesthetic realities in a field of particular perception that becomes public, particularly today in a post-conventional social context. This paper reflects on this process of post-conventional change in which visual culture is situated and in which photography and memory are increasingly involved, weaving new identities.